OPTIMALISASI TUGAS SUB BAGIAN PROTOKOL DALAM MELAKUKAN PROGRAM KERJA KEGIATAN BERDASARKAN PERATURAN GUBERNUR NO MOR 60 TAHUN 2016 PASAL 25 AYAT (2) HURUF A DI DPRD PROVINSI LAMPUNG - Agusman Hari; Prasetyawati S. Endang (Universitas Bandar Lampung (UBL), 2022)
Protocol is regulated in Law No. 9 of 2010 concerning Protocol. By definition of law. The Minister reports that protocol is a series of activities related to provisions in state activities or formal activities which include place arrangements, ceremonial procedures, and honors as a form of respect for someone according to his position and/or role in the country, government, or citizens. State activity is an activity that is regulated and carried out by a centralized state committee, which visits are the President and/or Vice President, and State Officials and other invitees. Next, formal activities are activities that are regulated and carried out by the government or state institutions in carrying out certain tasks and purposes, those attending are state officials and/or government officials and other invitees. Then a very basic comparison between activities.state with activities. Formal government is the central government and regional government together can carry out formal activities but state activities can only be held by a state committee. State activities are regulated and carried out by the state committee, whereas formal activities are regulated by protocol officers who are part of government institutions. Problems How to Optimize Article 25 Paragraph (2) Letter A Regarding the Task of Performing Work Program Activities Sub-Section Protocol Governor Regulation Number 60 Year 2016 .The research method uses a normative and empirical juridical approach. The data used are secondary data and primary data. The data analysis used is qualitative juridical analysis. DiscussionOptimizing the duties and functions of the preparation of the protocol work program of the Regional People's Representative Council based on article 25 paragraph 2 regarding the task of carrying out the work program of the protocol sub-section activities according to the Lampung provincial governor regulation number 60 of 2016 that there is a need for two-way communication between the protocol and the work program drafting committee Lampung Provincial People's Representative Council in order to be more optimal.